Business Strategy for Sustainable Barbershop Partnership (Case Study: Kolega Barber) - fadillah, galih; Suhaimi, Hasnul; Sunitiyoso, Yos (Cv. Syntax Corporation Indonesia, 2023)
The barbershop industry in Indonesia has seen significant growth in recent years, with an annual growth rate of 20-30%. Kolega Barber is one of the players in this industry, utilizing a partnership model to target entrepreneurs and foster collaboration among stakeholders. However, the lack of standardization in the interior of the barbershops poses a significant challenge, making it difficult for potential partners to know what to expect. This study aims to analyze the current business situation of Kolega Barber's partnership model and develop a sustainable partnership model by addressing challenges identified through a 7Ps analysis. The study employs qualitative research methods, including interviews with Kolega partners and observation. The Development of a Business Model Canvas was utilized to create a model of sustainable partnership for Kolega Barber. This involved identifying the essential partners, resources, activities, and revenue streams for the business's success. The strategic implementation plan focuses on SOP development, human capital development, monitoring and controlling programs, and promotional support. Kolega Barber's long-term success and customer loyalty depend on building strong partnerships, leveraging technology, and emphasizing sustainability and a unique store concept.